Challenges and Opportunities in Adopting Capital Budgeting Practices - Ika Sari Wahyudi (PT. BERBAGI TEKNOLOGI SEMESTA, 2023)
This study aims to examine the obstacles and potential advantages that small and medium firms encounter when using capital budgeting techniques. The present study employs a design that involves doing a comprehensive literature analysis to analyze various papers and prior research. The present study reveals a number of problems encountered by small and medium firms in the process of adopting capital budgeting techniques. One of the most significant obstacles that has a profound impact is the deficiency in understanding capital budgeting. The implementation of capital budgeting procedures is infrequently observed among small and medium firms, resulting in limited impact. Despite the potential benefits it offers to the development of small and medium firms, capital budgeting facilitates crucial decision-making processes pertaining to investments, long-term planning, and investment assessment for business owners. The practical implication of this study suggests that owners of small and medium firms should consider enhancing their financial knowledge or seeking professional experience in the areas of finance and management.